Can a Mobile-App-Based Behavioral Intervention Teach Financial Skills to Youth? Experimental Evidence from a Financial Diaries Study - Veronica Frisancho; Alejandro Herrera; Silvia Prina (Institute of Labor Economics (IZA), 2023)
We study the impact of a mobile-app-based behavioral intervention on youth's financial literacy and financial behavior. To maximize the chances to reach out-of-school youth, we provided access to a user-friendly budget recording tool coupled with biweekly enumerators' visits and SMSs during a 27-week period. The bundled treatment has positive and significant effects on financial literacy and awareness of market prices. The probability of saving and savings deposits are not affected, but usage of credit increases both at the extensive and intensive margins. Average treatment effects on financial literacy and behavior are driven by youth without previous exposure to financial education, suggesting that the bundled intervention prompted specific subgroups (i.e., youth with lower levels of financial knowledge) to invest more in financial literacy.
Keywords: C93; D90; G41; G53; O12; O16; 330; financial inclusion; financial diaries; financial literacy; youth